2023
DOI: 10.21203/rs.3.rs-2479032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cone-Beam Computed Tomographic Analysis of Maxillary Sinus Septa among Yemeni Population A Cross-sectional study

Abstract: Background Maxillary sinus septa increase perforation risk of Schneiderian membrane during the sinus floor elevation (SFE). Cone Beam Computed Tomography (CBCT) allows for a more precise assessment of the septal position; thus, preoperative CBCT analysis is substantial to avoid possible complications. This study aims to investigate the 3D characteristics of the maxillary sinus septa based on CBCT images. To our knowledge, no study reported the CBCT-based investigation for the sinus septa among Yemeni populati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Other investigations that contradict the current findings [6] found that right-side septa were more prevalent [6,21]. However, Altayar et al observed that the left side was more dominant than the right side, consistent with our findings [22]. Other researchers, such as Paknahad et al, attempted to compare the frequency of sinus septa in cleft and non-cleft individuals and observed no difference in the prevalence of MSS between patients with cleft lip and palate (CLP) and non-CLP individuals [23].…”
Section: Discussionsupporting
confidence: 90%
“…Other investigations that contradict the current findings [6] found that right-side septa were more prevalent [6,21]. However, Altayar et al observed that the left side was more dominant than the right side, consistent with our findings [22]. Other researchers, such as Paknahad et al, attempted to compare the frequency of sinus septa in cleft and non-cleft individuals and observed no difference in the prevalence of MSS between patients with cleft lip and palate (CLP) and non-CLP individuals [23].…”
Section: Discussionsupporting
confidence: 90%
“…Computed Tomography (CT) scans offer precise evaluations of paranasal sinuses, including sinus pneumatization. CT scans provide cross-sectional and three-dimensional information, commonly available in hospitals (7).…”
Section: Introductionmentioning
confidence: 99%